Combination immunohistochemistry for SMAD4 and Runt-related transcription factor 3 may identify a favorable prognostic subgroup of pancreatic ductal adenocarcinomas - Lee, Yangkyu (Oncotarget, 2017)
PURPOSES: SMAD4/DPC4 mutations have been associated with aggressive behavior in pancreatic ductal adenocarcinomas (PDAC), and it has recently been suggested that RUNX3 expression combined with SMAD4 status may predict the metastatic potential of PDACs. We evaluated the prognostic utility of SMAD4/RUNX3 status in human PDACs by immunohistochemistry. MATERIALS AND METHODS: Immunohistochemical stains were performed for SMAD4 and RUNX3 on 210 surgically resected PDACs, and the results were correlated with the clinicopathological features. RESULTS: Loss of SMAD4 expression was associated with poor overall survival (OS) (p = 0.015) and progression-free survival (PFS) (p = 0.044). Nuclear RUNX3 expression was associated with decreased OS (p = 0.010) and PFS (p = 0.009), and more frequent in poorly differentiated PDACs (p = 0.037). On combining RUNX3/SMAD4 status, RUNX3-/SMAD4+ PDACs demonstrated longer OS (p = 0.008, median time; RUNX3-/SMAD4+ 34 months, others 17 months) and PFS (p = 0.009, median time; RUNX3-/SMAD4+ 29 months, others 8 months) compared to RUNX3+/SMAD4+ and SMAD4- groups; RUNX3-/SMAD4+ was a significant independent predictive factor for both OS [p = 0.025, HR 1.842 (95% CI 1.079-3.143)] and PFS [p = 0.020, HR 1.850 (95% CI 1.100-3.113)]. CONCLUSIONS: SMAD4-positivity with RUNX3-negativity was a significant independent predictive factor for favorable OS and PFS in PDAC. This is the first and large clinicopathological study of RUNX3/SMAD4 expression status in human PDAC. Combination immunohistochemistry for SMAD4 and RUNX3 may help identify a favorable prognostic subgroup of PDAC.